A Igreja entendida como comunhão a partir da relação trinitária e suas implicações na atual vida eclesial - Silva, Rodrigo Antonio da (2018)
Hermetic definitions about the Church can not to express the fullness of her Mystery. Overcoming the vision of juridical emphasis, the ecclesiology developed from the Second Vatican Council takes the theological way of the first millennium and rescues aspects, images and notions that complement each other. The Church recognizes herself as being a mystery: desired by God, she has her foundation, life and destiny in the Trinity. Your life should express Trinitarian communion. It is the new People of God who walk in communion with each other and with God towards the heavenly homeland. Evidently, this vision rescued and renewed in the Council brings with it new ecclesial relations ad intra and ad extra. The Ecclesiology of Communion, along with other important images and definitions, still seems to lack more attention and also remains with an immense open field of practical applications in the ecclesial life. The present dissertative text intends to explore the foundations and relevance of this ecclesiology for the present time and the possible implications already observed in some scenarios of the Church. For this purpose, the author offers the results of the research in three moments: first, he presents the fundamental biblical concepts that relate to the ecclesiology of communion: community, communion and People of God. Next, the contrast between the juridical ecclesiology characteristic of the second millennium and the paradigm shift present in the Dogmatic Constitution Lumen Gentium, as well as some advances achieved in the trinitarian and ecclesiological theologies in the post-Council, is made. Finally, the focus is on some of the ecclesial articulations developed in recent years: the dialogue movement in the internal and external spheres of the Church, the reception in Latin America, as well as the perspectives opened from the pontificate of Pope Francis